Re-Use and Recycling of Materials : Solid Waste Management and Water Treatment. - Nzihou, Ange; Thomas, Sabu; Kalarikkal, Nandakumar; Jibin, K. P. (River Publishers Series in Chemical, Environmental, and Energy Engineering Ser., 2019)
In recent years, a considerable amount of effort has been devoted, both in industry and academia, towards the recycling and reuse of materials. Most nations are now trying to reduce the amount of waste materials, through the proper recycling of materials.Re-Use and Recycling of Materials will help readers to understand the current status in the field of waste management, as well as what research is taking place to deal with such issues.Technical topics discussed in the book include: Municipal solid waste management Recycling of WEEE Waste to industrially important product like lignin and cellulose Recycling of agriculture waste Polymer and plastic recycling